Neurological Disorders in Takotsubo Syndrome: Clinical Phenotypes and Outcomes - Francesco Santoro; Iván J. Núñez Gil; Luca Arcari; Enrica Vitale; Tommaso Martino; Ibrahim El‐Battrawy; Federico Guerra; Giuseppina Novo; Enrica Mariano; Beatrice Musumeci; Luca Cacciotti; Pasquale Caldarola; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Neurological disorders as a risk factor for Takotsubo syndrome (TTS) are not well characterized. The aim of the study was to evaluate TTS‐associated neurological phenotypes and outcome. Methods and Results Patients with TTS enrolled in the international multicenter GEIST (German Italian Spanish Takotsubo) registry were analyzed. Prevalence, clinical characteristics, and short‐ and long‐term outcomes of patients with TTS were recorded. A subgroup analysis of the 5 most represented neurological disorders was performed. In total, 400 (17%) of 2301 patients had neurological disorders. The most represented neurological conditions were previous cerebrovascular events (39%), followed by neurodegenerative disorders (30.7%), migraine (10%), epilepsy (9.5%), and brain tumors (5%). During hospitalization, patients with neurological disorders had longer in‐hospital stay (8 [interquartile range, 5–12] versus 6 [interquartile range, 5–9] days; P<0.01) and more often experienced in‐hospital complications (27% versus 16%; P=0.01) mainly driven by cardiogenic shock and in‐hospital death (12% versus 7.6% and 6.5% versus 2.8%, respectively; both P<0.01). Survival analysis showed a higher mortality rate in neurological patients both at 60 days and long‐term (8.8% versus 3.4% and 23.5% versus 10.1%, respectively; both P<0.01). Neurological disorder was an independent predictor of both the 60‐day and long‐term mortality rate (odds ratio, 1.78 [95% CI, 1.07–2.97]; P=0.02; hazard ratio, 1.72 [95% CI, 1.33–2.22]; both P<0.001). Patients with neurodegenerative disorders had the worst prognosis among the neurological disease subgroups, whereas patients with TTS with migraine had a favorable prognosis (long‐term mortality rates, 29.2% and 9.7%, respectively). Conclusions Neurological disorders identify a high‐risk TTS subgroup for enhanced short‐ and long‐term mortality rate. Careful recognition of neurological disorders and phenotype is therefore needed.